Introduction to Digital Work in the Planetary Market - Mark Graham; Fabian Ferrari (Journal of Economic Sociology, 2025)
Many types of work can be performed from anywhere in the world today. Digital technologies and ubiquitous Internet access allow almost everyone to connect with anyone to communicate and share files, data, video and audio. In other words, work can be deterritorialized on a global scale. This book explores the consequences of such a situation for work and employees, when labor becomes a commodity and goes beyond local markets. Going beyond the usual discworld-style arguments about globalization, the authors analyze both the transformation of work itself and the broader systems, networks, and processes that make digital work possible in the planetary market, offering both empirical and theoretical analysis. The authors, leading scientists and experts from various fields, address various issues, including content moderation, autonomous vehicles, and voice assistants. First, they explore new work experiences and discover that, despite the planetary connections, work remains geographically anchored and embedded in certain contexts. They then analyze ways to map and problematize planetary labor networks, discuss the productivity of using diverse and interdisciplinary approaches in the study of digital labor and its networks, and finally propose options for regulating planetary labor. The journal of Economic Sociology publishes an introduction to the book, where M. Graham and F. Ferrari problematize the increasing commodification and globalization of labor as a result of the expansion of digital technologies.